Expression profiles of 151 pediatric low-grade gliomas reveal molecular differences associated with location and histological subtype. Issue 11 (29th March 2015) - Bergthold, Guillaume; Bandopadhayay, Pratiti; Hoshida, Yujin; Ramkissoon, Shakti; Ramkissoon, Lori; Rich, Benjamin; Maire, Cecile L.; Paolella, Brenton R.; Schumacher, Steven E.; Tabak, Barbara; Ferrer-Luna, Ruben; Ozek, Memet; et al.
Abstract: Background: Pediatric low-grade gliomas (PLGGs), the most frequent pediatric brain tumor, comprise a heterogeneous group of diseases. Recent genomic analyses suggest that these tumors are mostly driven by mitogene-activated protein kinase (MAPK) pathway alterations. However, little is known about the molecular characteristics inherent to their clinical and histological heterogeneity. Methods: We performed gene expression profiling on 151 paraffin-embedded PLGGs from different locations, ages, and histologies. Using unsupervised and supervised analyses, we compared molecular features with age, location, histology, and BRAF genomic status. We compared molecular differences with normal pediatric brain expression profiles to observe whether those patterns were mirrored in normal brain. Results: Unsupervised clustering distinguished 3 molecular groups that correlated with location in the brain and histological subtype. "Not otherwise specified" (NOS) tumors did not constitute a unified class. Supratentorial pilocytic astrocytomas (PAs) were significantly enriched with genes involved in pathways related to inflammatory activity compared with infratentorial tumors. Differences based on tumor location were not mirrored in location-dependent differences in expression within normal brain tissue. We identified significant differences between supratentorial PAs and diffuse astrocytomas as well as between supratentorial PAs and dysembryoplastic neuroepithelial tumors but not between supratentorial PAs and gangliogliomas. Similar expression patterns were observed between childhood and adolescent PAs. We identified differences between BRAF -duplicated and V600E-mutated tumors but not between primary and recurrent PLGGs. Conclusion: Expression profiling of PLGGs reveals significant differences associated with tumor location, histology, and BRAF genomic status. Supratentorial PAs, in particular, are enriched in inflammatory pathways that appear to be tumor-related.